Knowledge, Attitude, and Practice of Jinka University Students About Yellow Fever, Ethiopia: A Cross-Sectional Study - Endale A; Medhin G; Hilo AA; Abegaz WE; Legesse M (Dove Medical Press, 2020)
Adugna Endale,1,2 Girmay Medhin,1 Abdela Alte Hilo,3 Woldaregay Erku Abegaz,4 Mengistu Legesse1 1Aklilu Lemma Institute of Pathobiology, Addis Ababa University, Addis Ababa, Ethiopia; 2School of Medicine, College of Medicine and Health Sciences, Dire Dawa University, Dire Dawa, Ethiopia; 3Jinka University, Jinka, Ethiopia; 4Department of Microbiology, Immunology & Parasitology, School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Adugna Endale Email adugna.endale@aau.edu.etBackground: Yellow fever (YF) is endemic in South Omo area of Ethiopia. Although Jinka University (JKU) is located in South Omo Zone, there is no information regarding the level of knowledge, attitude, and practice of students toward YF. The current study aimed to assess knowledge, attitude, and practice of JKU students toward YF and factors associated with the overall knowledge and attitude about the disease.Methods: In this cross-sectional study, a semi-structured self-administered questionnaire was used to collect data from randomly selected regular program JNU students. Data were analyzed using SPSS. Bivariate and multivariable logistic regression analyses were performed to investigate associations of socio-demographic factors with overall knowledge and attitude scores.Results: A total of 322 students (61.2% males, mean age of 20.7 years) participated in this study. Of these, 94.1% joined the University from places other than South Omo area and 86.0% (277/322) ever heard about YF. 9.6% were found to have a high level of overall knowledge about YF. High overall knowledge of YF was associated with being born and grown up in South Omo area (AOR=3.91; 95% CI: 1.28, 11.98) and being a student of a social science discipline (AOR=3.52; 95% CI: 1.22, 10.13). 48.8% of the participants had favorable overall attitude toward YF. Being a second-year student (AOR=1.96; 95% CI: 1.14– 3.37), being born and grown up in South Omo area (AOR=5.13; 95% CI: 1.32– 19.98), and having high overall knowledge of YF (AOR=13.24; 95% CI: 3.69, 47.44) were associated with favorable overall attitude toward YF. On the other hand, only 5.8% of the participants reported that they were vaccinated for YF.Conclusion: The low level of knowledge and low vaccination coverage of JKU students to YF, especially among those students from other parts of the country, calls for urgent awareness creation during admission and making vaccination available.Keywords: yellow fever, knowledge, attitude, practice, student, Ethiopia